Effects of Fraud-Triangle Decomposition on Sensitivity and Quality of Auditor’s Fraud Risk Assessment Based on Iranian Auditing Standard Number # 240 - Abdollah Khani (Shahid Bahonar University of Kerman, 2020)
Objective: Sas no. 99 in the U.S.A and Sas no. 240 in Iran by the requirement to decompose the misstatement risk to intentional and involuntary risks intended to increase the auditor’s ability to detect the fraud. But one of the biases that auditors always face in the fraud detection process is a lack of enough attention to relevant evidence in the auditing process. This bias could lead to misinterpretation of audit evidence and audit failures in detecting fraud. Applying a decomposition approach for a judgment to examining, comparing, and communicating between documents may lead auditors to hold detection systematically. Accordingly, this study examined the effects of applying holistic, decomposed, and grouping methods on the sensitivity and quality of senior auditor’s fraud risk assessments. Methods: This study is a causal-comparative, which used a 3*2 between-subjects factorial design and covariance analysis to test four hypotheses. In this research, the data obtained from a questionnaire and the sample consisting of senior auditors who are working in private auditing firms. In this study, 77 auditors assessed fraud risks, of which 42 auditors were assigned to the high and 35 auditors to low fraud risk conditions. These auditors used holistic, decomposed, and grouping methods for assessing fraud risk. Results: Covariance analysis showed that using the decomposed method leads to assessments of overall fraud risk, which is more sensitive to change in the level of fraud risk. In other words, using the decomposed method could increase the auditor’s attention to a high level of ls of fraud risk. But when comparing the two methods, the fraud risk assessments with decomposed and holistic methods were not significantly different. Also, assessment of the sensitivity of situational risk (opportunities and incentives) to changes in the level of fraud risk was not significantly different when using decomposed and holistic methods. Also, the results indicated that using decomposed and grouping methods cannot increase fraud risk quality. Surprisingly, in the holistic method, the auditor’s judgment was more consistent with the experts' judgments. Conclusion: The fraud issues are increasing in the world generally, and stockholders are more sensitive to these issues because of the impact on their investments. Because of this concern and as mentioned before in Sas no. 240 in Iran, Sas no. 99 in the U.S. required auditors to decompose the misstatement risk to intentional and involuntary risks to increase the auditors' ability to detect fraud. Based on the results, decomposition of the misstatement risk to intentional and unintentional risks can increase the auditors' ability to detect fraud.